PENERAPAN MODEL PEMBELAJARAN MEANS-ENDS ANALYSIS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA ELEMEN DESAIN PEMODELAN KONSTRUKSI JALAN JEMBATAN KELAS XI - Sem Yeremia Tarigan (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT The low learning outcomes of students in the Road and Bridge Construction Modeling Design subject encouraged this study through the implementation of the Means-Ends Analysis (MEA) learning model to improve students’ learning achievement. This study was conducted as Classroom Action Research (CAR) carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 31 students of class XI DPIB at SMK Negeri 5 Medan in the 2025/2026 academic year. Data were collected through observation, practical tests, and documentation, then analyzed using descriptive quantitative methods. The results showed that the implementation of the Means-Ends Analysis learning model significantly improved student learning outcomes. The average student learning outcome score in cycle I was 83, which had exceeded the minimum mastery criterion (KKM) of 75, but classical completeness had not yet been achieved, reaching only 70.97%. In cycle II, the average score increased to 88.74 with classical completeness reaching 93.55%. The increase in classical completeness from cycle I to cycle II was 22.58%. In addition, the median increased from 86 to 89, and the mode increased from 89 to 94. These results indicate an increase of 3 points in the median and 5 points in the mode. Therefore, the implementation of the Means-Ends Analysis learning model was proven effective in improving student learning outcomes in the Road and Bridge Construction Modeling Design subject for class XI DPIB students at SMK Negeri 5 Medan. ABSTRAK Rendahnya hasil belajar siswa pada mata pelajaran Elemen Desain Pemodelan Konstruksi Jalan dan Jembatan mendorong dilakukannya penelitian ini melalui penerapan model pembelajaran Means-Ends Analysis (MEA) untuk meningkatkan capaian belajar siswa. Penelitian ini merupakan penelitian tindakan kelas (PTK) yang dilaksanakan dalam dua siklus, masing-masing terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas XI DPIB SMK Negeri 5 Medan tahun ajaran 2025/2026 yang berjumlah 31 orang. Data dikumpulkan melalui observasi, tes praktik, dan dokumentasi, kemudian dianalisis secara deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran Means-Ends Analysis dapat meningkatkan hasil belajar siswa secara signifikan. Nilai rata-rata hasil belajar siswa pada siklus I sebesar 83 telah melampaui KKM 75, namun belum memenuhi ketuntasan klasikal yaitu 70,97%. Pada siklus II, nilai rata-rata meningkat menjadi 88,74 dengan ketuntasan klasikal sebesar 93,55%. Peningkatan ketuntasan klasikal dari siklus I ke siklus II mencapai 22,58%. Selain itu, median meningkat dari 86 menjadi 89, dan modus meningkat dari 89 menjadi 94. Hasil tersebut menunjukkan adanya peningkatan nilai median sebesar 3 dan modus sebesar 5. Dengan demikian, penerapan model pembelajaran Means-Ends Analysis efektif dalam meningkatkan hasil belajar siswa pada elemen Desain Pemodelan Konstruksi Jalan dan Jembatan di kelas XI DPIB SMK Negeri 5 Medan.